The Determinants of Meat Import Performance in ASEAN Countries - Putri, Adelia Erlita; Sulistiyani, Endang; Indrasari, Febrina (Jurnal Manajemen Bisnis, 2021)
Research aims: The objective of this research is to analyze the effect of Gross Domestic Product, exchange rate, and distance on the meat import performance of ASEAN countries both partially and simultaneously.Design/Methodology/Approach: Purposive sampling method was adopted to determine the research sample. The data used were the annual secondary data of ASEAN countries in the period of 2012-2018, collected from trademap.org, World Bank, and macmap.org. Multiple Linear Regression was employed to analyze the data.Research findings: The regression analysis results showed that GDP and exchange rate did not affect meat import performance. Meanwhile, distance had a partially significant negative effect on meat import. However, GDP, exchange rate, and distance had a significant effect on meat imports simultaneously.Theoretical contribution: Previous researchers have used economic distance in their study to see its impact on imports. Nevertheless, there has not been much research done using geographical distance as an antecedent variable. The distant market has to incur large-fixed costs, which can only be supported if the export value is large. The negative impact of distance on imported meat must be taken seriously. AANZFTA supposedly gives a contribution to the member countries thoroughly to export goods and services. It is to increase per capita income so that it can be used to improve the transportation system.Implication policy: ASEAN officials are suggested to encourage the member countries to provide better transportation facilities to eliminate geographical distance barriers and further support SMEs and other business actors' engagement. Due to the limitation of this research, it is suggested that further research should consider using other commodities to measure the import performance.